2009
DOI: 10.1038/hdy.2008.128
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of outcrossing rates at hierarchical levels of fruits, individuals, populations and species in Magnolia stellata

Abstract: In plant species with mixed mating systems, differences in diverse factors-including their pollination system, flowering phenology, life form and susceptibility to inbreeding depression-cause variation in outcrossing rates among fruits within individuals, among individuals within populations and among populations within species. To quantify this hierarchical variation, we examined outcrossing rates at the seed stage in five populations of Magnolia stellata, a self-compatible, insect-pollinated and protogynous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
4
16
0
Order By: Relevance
“…Thus, most of the fruits appeared to contain full-sibs. A higher paternity correlation within rather than among fruits has been detected in other plant species (Muona et al, 1991;Sampson, 1998;Quesada et al, 2001;Tamaki et al, 2009). …”
Section: Correlated Matingmentioning
confidence: 70%
“…Thus, most of the fruits appeared to contain full-sibs. A higher paternity correlation within rather than among fruits has been detected in other plant species (Muona et al, 1991;Sampson, 1998;Quesada et al, 2001;Tamaki et al, 2009). …”
Section: Correlated Matingmentioning
confidence: 70%
“…An increase in self-fertilization in logged or fragmented populations in comparison to undisturbed populations has also been reported for some tropical tree species (Murawski et al 1994;Aldrich and Hamrick 1998;Cascante et al 2002;Fuchs et al 2003;Lobo et al 2005;Tamaki et al 2009). For example, Paquira quinata, Ceiba pentandra and Samanea saman occurring in continuous forests appear to be self-incompatible; however, in fragmented populations or as isolated trees in pastures, these species show some levels of self-fertilization and a shift to a mixed-mating system (Cascante et al 2002;Fuchs et al 2003;Lobo et al 2005).…”
Section: Introductionmentioning
confidence: 81%
“…However, this difference is always an underestimate as it depends upon the number of loci used: the more loci used, the closer to the true difference (Ritland 2002). Each parameter was examined at several hierarchical levels (Ritland 1989;Muona et al 1991;Quesada et al 2001;Tamaki et al 2009, Silva et al 2011: between populations; among trees within a population; and among and within fruits of the same seed-tree. Analyses at the population level were carried out using the Newton-Raphson numerical method and at the individual and fruit levels using the Expectation-Maximization numerical method.…”
Section: Mating System Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Tan et al (2012) also found a non-significant difference in the t m values (ranging from 1.033 to 1.200) of 8 individuals obtained from a seed orchard of P. massoniana. However, De-Lucas et al (2008) showed that there was a significant difference in the t m values among P. pinaster individuals growing across areas in the Mediterranean region, which may be co-determined by abiotic factors across areas and biotic factors such as florescence synchronism, tree height, and canopy size among individuals in different populations (Tamaki et al, 2009).…”
Section: Stability Of the Mating Systemmentioning
confidence: 99%